A Comparative Study on the Effectiveness and Satisfaction of Using Ya-Tha-Pra-Sen Hydrogel Patches and Herbal Poultice Form to Reduce Plantar Pain in Personnel and Students, Sirindhorn College of Public Health, Trang Province - Udompittayason, Jadsada; Ramanje, Firdaus; Ouseng, Lawhayu; Issarachot, Ousanee; Arunotayanun, Warunya (Princess of Naradhiwas University Journal, 2026)
Background and Objectives This quasi-experimental study aimed to compare the effectiveness and satisfaction of using Ya-Tha-Pra-Sen hydrogel patches and herbal poultice form for relieving plantar pain in personnel and students of the Sirindhorn College of Public Health, Trang Province. Methods A sample of 80 participants was selected and divided into two groups. Group 1 used Ya-Tha-Pra-Sen hydrogel patches applied to the painful plantar area once a day for 30 minutes, then removed, while group 2 received the Ya-Tha-Pra-Sen herbal poultice form applied to the painful plantar area once a day for 30 minutes, then washed off. This was done continuously for 3 days in both groups. Effectiveness was evaluated using the Visual Analogue Scale (VAS) Foot and Ankle (Thai Version) to assess the degree of ankle movement with the plantarflexion position and to evaluate satisfaction with product use. Results After using both forms for 3 days, it was found that they were effective in reducing plantar pain severity and increasing ankle range of motion, with no statistically significant difference (p<.05). However, users of the Ya-Tha-Pra-Sen Hydrogel patch form were more satisfied with the product than the group using the Ya-Tha-Pra-Sen Herbal Poultice form, as it was convenient to use and the product had an appealing appearance. Conclusion and Recommendatio: Ya-Tha-Pra-Sen hydrogel patches are an alternative product for developing traditional herbal formulas to be convenient and effectively relieve pain and can be applied to plantar fasciitis.